Phagocytic response and phenoloxidase activity of the hemocytes of Bellamya bengalensis exposed to synthetic fenvalerate - Suman Mukherjee; Chiranjib Mandal (Journal of Stress Physiology & Biochemistry, 2023)
Background: Bellamya bengalensisis an important bioresource of the freshwater ecosystem of India. This edible mollusc is filter feeder, indigenous diet of human, poultry and fishery. Natural habitat of this freshwater gastropod mollusc bears the risk of contamination by agricultural pesticide fenvalerate, a synthetic type II pyrethroid. Hemocytes are the immuno effector cells of molluscs which are affected by environmental toxins or pathogenic microorganisms. Hemocytes perform various types of immunological functions such as phagocytosis, cytotoxic response etc. Results: Experimental exposure of fenvalerate resulted in impairment of phagocytic efficacy and alteration in the generation of phenoloxidase in B. bengalensis. Conclusion: The alteration of phagocytic response and generation of phenoloxidase of hemocytes, exposed to experimental concentrations of fenvalerate under static laboratory condition have been determined to establish as biomarker of aquatic toxicity in toxin contaminated natural habitat.